Association between cerebrospinal fluid biomarkers of neuronal injury or amyloidosis and cognitive decline after major surgery. (February 2021) - Danielson, Mattias; Wiklund, Andreas; Granath, Fredrik; Blennow, Kaj; Mkrtchian, Souren; Nellgård, Bengt; Oras, Jonatan; Fagerlund, Malin J.; Granström, Anna; Schening, Anna; Rasmussen, Lars S.; Harris, Helena E.; et al.
Abstract: Background: Postoperative neurocognitive decline is a frequent complication in adult patients undergoing major surgery with increased risk for morbidity and mortality. The mechanisms behind cognitive decline after anaesthesia and surgery are not known. We studied the association between CSF and blood biomarkers of neuronal injury or brain amyloidosis and long-term changes in neurocognitive function. Methods: In patients undergoing major orthopaedic surgery (knee or hip replacement), blood and CSF samples were obtained before surgery and then at 4, 8, 24, 32, and 48 h after skin incision through an indwelling spinal catheter. CSF and blood concentrations of total tau (T-tau), neurofilament light, neurone-specific enolase and amyloid β (Aβ1-42) were measured. Neurocognitive function was assessed using the International Study of Postoperative Cognitive Dysfunction (ISPOCD) test battery 1–2 weeks before surgery, at discharge from the hospital (2–5 days after surgery), and at 3 months after surgery. Results: CSF and blood concentrations of T-tau, neurone-specific enolase, and Aβ1-42 increased after surgery. A similar increase in serum neurofilament light was seen with no overall changes in CSF concentrations. There were no differences between patients having a poor or good late postoperative neurocognitive outcome with respect to these biomarkers of neuronal injury and Aβ1-42. Conclusions: The findings of the present explorative study showed that major orthopaedic surgery causes a release of CSF markers of neural injury and brain amyloidosis, suggesting neuronal damage or stress. We were unable to detect an association between the magnitude of biomarker changes and long-term postoperative neurocognitive dysfunction.